Analysis of Community Adaptation Strategies Factors for Ecosystem-Based Disaster Risk Reduction in the Upper Merawu Watershed - Nurika Arum Sari; Hatma Suryatmojo; Arini Wahyu Utami; Nela Agustin Kurniangisih (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2023)
The Merawu Watershed is one of the critical watersheds in Indonesia. This watershed is located in Banjarnegara Regency which has an altitude of 1000 meters above sea level with high rainfall intensity. The type of soil in Banjarnegara Regency is mostly ultisol and inceptisol soil, making the area vulnerable to landslides. Under these conditions, intensive agriculture is mostly carried out by the surrounding community, with the main commodity being planted is potatoes. Planting without paying attention to soil and water conservation techniques on steep land and spraying pesticides with high intensity can trigger erosion, landslides, and environmental pollution. The hamlets of Tamansari and Penanggungan are prone to erosion, landslides, and environmental pollution due to intensive agriculture. But, the adaptation strategy adopted by the community is still lacking. Therefore, it is necessary to research the factors that influence community adaptation strategies in ecosystem-based disaster risk reduction. This study aims to identify the factors that influence the adaptation strategy. The method used in this research is the logit model method. The respondents used in this study were 30 from the Tamansari Hamlet and the Penanggungan Hamlet. The results showed that the adaptation strategies factors for erosion are land area and household income, while landslides are assets and location. There are no variables that have a significant effect on the community's adaptation strategy to environmental pollution.